2001
DOI: 10.1007/pl00011235
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibilities Among Recent Clinical Isolates of Haemophilus influenzae and Moraxella catarrhalis from Fifteen Countries

Abstract: Between July 1998 and July 1999, 3,060 Haemophilus influenzae and 1,486 Moraxella catarrhalis strains were isolated in 31 centers in 15 countries in order to determine their antimicrobial susceptibilities and the presence of beta-lactamase production in Haemophilus influenzae. Overall 17.1% of the Haemophilus influenzae isolates were beta-lactamase positive, while more than 95% were susceptible to amoxicillin/clavulanate, cefaclor, loracarbef, cefuroxime, azithromycin and ciprofloxacin. Eleven (0.3%) isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In the lower respiratory tract, M. catarrhalis can cause respiratory infections in adults with chronic obstructive pulmonary disease, resulting in increased morbidity and mortality of these patients (27,28). M. catarrhalis is thought to be responsible for 2 to 4 million infectious exacerbations of chronic obstructive pulmonary disease in the United States each year (25), and there is significant cost in treating disease related to M. catarrhalis, which is complicated in part by a rise in antibiotic-resistant strains (2,30). This makes development of a vaccine an exciting and important goal.…”
mentioning
confidence: 99%
“…In the lower respiratory tract, M. catarrhalis can cause respiratory infections in adults with chronic obstructive pulmonary disease, resulting in increased morbidity and mortality of these patients (27,28). M. catarrhalis is thought to be responsible for 2 to 4 million infectious exacerbations of chronic obstructive pulmonary disease in the United States each year (25), and there is significant cost in treating disease related to M. catarrhalis, which is complicated in part by a rise in antibiotic-resistant strains (2,30). This makes development of a vaccine an exciting and important goal.…”
mentioning
confidence: 99%
“…Clinical and epidemiological studies revealed high carriage rates in young children and suggested that a high rate of colonization was associated with an increased risk of the development of M. catarrhalis-mediated diseases (28). In addition, the number of antibiotic-resistant strains of M. catarrhalis has increased significantly over the past decades (5,18). Currently, the molecular pathogenesis of M. catarrhalis infection is not fully understood, and there is no vaccine to prevent M. catarrhalis infections (27).…”
mentioning
confidence: 99%
“…Sporadic cases of conjunctivitis, meningitis, endocarditis, ophthalmia neonatorum, keratitis, urethritis, peritonitis, and septicemia have also been reported in individuals with reduced immune defense (36). In addition, the number of antibiotic-resistant strains of M. catarrhalis has significantly increased over the past decades (3,23). Currently, the molecular pathogenesis of M. catarrhalis infection is not fully understood.…”
mentioning
confidence: 99%